Sosialisasi Dan Pembagian Masker Sebagai Upaya Pencegahan Penularan Covid 19 Di TK Sari Asih Sumbawa Besar - Gladeva Yugi Antari; Luh Putu Sri Yuliastuti (Pusat Riset dan Inovasi Nasional, 2022)
Efforts to reduce the transmission of COVID-19 are still being encouraged, by carrying out various precautions, especially in school areas. The transmission of SARS-Cov-2 (Covid-19) is faster than SARS-Cov and MERS-Cov. Signs and symptoms of this disease include acute respiratory distress, such as fever, cough and shortness of breath. Judging from the situation of the spread of covid 19 which has almost reached all provinces in Indonesia with the number of cases and/or the number of deaths increasing and having an impact on the political, economic, social, cultural, defense and security aspects, as well as the welfare of the Indonesian people. In the context of tackling COVID-19, Indonesia has established a new normal (new order) so that people can adapt to COVID-19, namely by continuing to apply the Health protocol, namely using masks, maintaining distance and washing properly according to the recommendations of the Ministry of Health. The purpose of this service is to increase awareness and implementation of health protocols as a form of preventing Covid-19. The method in this service is to provide masks and socialize the use of masks with a total of 30 kindergarten students. After counseling the students have used masks correctly. This is based on the results of observations during the activity. The results obtained that all students have used masks. So it can be concluded that there is an increase in the use of masks in Sari Asih Kindergarten students.